DIGITAL DIVIDE IN THE PROVISION OF ETHICAL AND VALUES EDUCATION: RE-ENGINEERING FOR SUSTAINABLE NATIONAL DEVELOPMENT (Journal of Association of Educational Management and Policy Practitioners, 2026)
This paper investigates the complex and multidimensional ways in which the digital divide undermines the delivery and accessibility of ethical and values education, which are critical foundations for sustainable national development. Ethical and values education foster moral reasoning, civic engagement, empathy, integrity, and social responsibility all of which are indispensable for building just, inclusive, and forward-looking societies. However, disparities in access to digital infrastructure, connectivity, digital skills, and relevant content collectively known as the digital divide create educational inequalities that limit the reach and effectiveness of moral education, especially in developing regions such as sub-Saharan Africa.Drawing on empirical studies, global policy frameworks, and theoretical models, this paper analyzes how the digital divide manifests in three primary forms: (1) access divide (limited access to devices and internet), (2) skills divide (inadequate digital literacy among teachers and learners), and (3) usage divide (low engagement with ICT for meaningful educational purposes). These divides exacerbate existing inequalities in the moral formation of learners and hinder national aspirations for responsible citizenship and sustainable development. The researcher further proposes re-engineering approaches that integrate inclusive infrastructure planning, digital content development, teacher professional development, and culturally relevant policies for ethics instruction through ICT. Case studies from Africa, alongside frameworks like UNESCO's Qingdao Declaration and SDG4, are used to illustrate successful strategies and ongoing challenges. By bridging the digital divide, nations can strengthen ethical and values education as a catalyst for sustainable national transformation.